Haptic Cushion for Conveying Navigation Cues. - Trujillo-León, Andrés; Vidal-Verdú, Fernando; Remache-Vinueza, Paul; Villaba-Bravo, Rafael; Álvarez-Crespo, Ana (IEEE, 2025)
The number of devices that provide information through haptic feedback keeps growing due to their applications in biomedicine, industry, or entertainment. This paper presents a haptic cushion that conveys navigation cues to the user seated atop it. The device comprises an MDF base equipped with actuators and covered with a commercial cushion. The generation of different cues is achieved through tactile illusions of motion, which allow the use of fewer actuators while creating smooth motion perceptions. Two experiments were conducted to evaluate the device. In the first one, volunteers were tasked with identifying the motion cue conveyed by the cushion from five given options. The results indicated that most participants could differentiate the motion patterns with a reasonable degree of confidence. The second experiment assessed the haptic cushion as a tool to provide motion commands in a navigation task, namely a treasure hunt game. Participants were instructed to navigate a map of squares, following the trajectory indicated by the cushion. Almost 70% of them demonstrated a perfect performance, with 16% exhibiting a single error and 8% committing two errors. The results appear to support the proposal’s viability.
https://journals.ieeeauthorcenter.ieee.org/become-an-ieee-journal-author/publishing-ethics/guidelines-and-policies/post-publication-policies/
Keywords: Ingeniería biomédica; Tacto; Psicología fisiológica; Haptic cushion; Interface; Motion cue; Tactile illusion; Phantom motion; Cutaneous rabbit; Vibrotactile; Haptic feedback; Wearable; Cost-effective